PARTICIPATORY design for sustainable community development. - Hussein, Dina Bahaa Eldin (AUC Knowledge Fountain, 2019)

(untitled)
Over recent years, participatory design processes have been gaining momentum in the architecture field. This research analyzes the past experiences of the participatory design processes from literature and case studies to apply it on an ongoing sustainable development initiative for creating a dates pack-house in the Western Desert Oasis of El-Heiz. The aim of the development project of the dates pack-house at El-Heiz is to help achieve a more sustainable community economy. The research is done through understanding past intervention in the area, mapping the whole participatory design process (while being a design participant) in its various stages, and finally analyzing the outcomes. The methodology for mapping the process entails qualitative and quantitative assessments by being a participant observer documenting the whole process through observation, interviews, participatory action research and gathering numerical data. The project applies a triple bottom line sustainability analysis, and a critical assessment of the practicality of the building design for the operational process. This includes users’ feedback, modifications performed on the building, and the community impact. The study specifically answers questions -and raises others- about participatory design approach in architecture, while analyzing the potential of architecture in creating sustainable community economies in Egypt, especially through participatory design processes. This thesis also seeks to offer some recommendations for participatory sustainable design of community based commercial facilities.